PENGEMBANGAN LEMBAR KERJA SISWA DENGAN PENDEKATAN SAINTIFIK PADA MATERI BILANGAN KELAS VII MTs MUHAMMADIYAH 1 MALANG - Tondo, Abner Alosius Ama; Irianti, Nathasa Pramudita; Setiawan, Rudy (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
The development of LKS can help teaching and learning activities in the classroom especially during the covid-19 pandemic. Worksheets that are made in an attractive and systematic manner can help students to learn to be more active in learning mathematics. Choice of approach and model Learning is also something that plays a very important role in supporting development Interesting and systematic worksheets. The purpose of this study was to determine the feasibility of developing LKS with a scientific approach on the number material for class VII MTs Muhammadiyah 1 Malang. This research was a development research using the ADDIE development model which consists of five main stages, namely Analysis, Design, Development, Implementation, and Evaluation. The LKS developed was validated by three validators, namely two mathematics education lecturers and a seventh grade mathematics teacher. The quality of the LKS with a scientific approach that was developed was assessed from the aspects of media, language and material with an average validation result of 83.12%. The subject of the experiment was carried out on class VII A students of MTs Muhammadiyah 1 Malang with a total of 23 students. Data collection techniques were carried out by interviews, validation, tests and questionnaires. Based on the results of the small group trial, an average percentage score of 80.45% showed that the LKS was very valid, in the large group the LKS that the researchers developed got a very interesting response with an average percentage score of 81.13%. So that the LKS compiled with a scientific approach is feasible to use.